Preparation method of low-Pt-loading high-temperature proton exchange membrane fuel cell anode catalyst, anode diffusion layer and membrane electrode

Through the preparation method of the high-temperature proton exchange membrane fuel cell anode catalyst for low Pt load, the problems of reduced catalyst activity and high cost in the high-temperature proton exchange membrane fuel cell system are solved, and the effects of high catalytic activity and anti-CO toxicity are achieved, which promotes the commercial application of the system.

CN119833648APending Publication Date: 2025-04-15INST OF ENERGY HEFEI COMPREHENSIVE NAT SCI CENT (ANHUI ENERGY LAB)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411821956.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the existing high-temperature proton exchange membrane fuel cell system, the poor binding force between phosphoric acid and polybenzimidazole leads to a spillover of phosphoric acid, resulting in a reduction in catalyst activity. The high cost of using a large number of precious metal Pt/C catalysts limits the development of the system, and the tolerance to high concentrations of CO is insufficient.

Method used

Using a high-temperature proton exchange membrane fuel cell anode catalyst with low Pt load, an anode catalyst with high catalytic activity and CO toxicity were prepared by preparing a mixed aqueous solution of alloy salt precursor and carbon support, and titrated addition of chloroplatinic acid aqueous solution and reducing agent aqueous solution to form a precipitate and undergo high-temperature reduction and calcination to prepare an anode catalyst with high catalytic activity and anti-CO toxicity.

Benefits of technology

It improves the activity of the anode catalyst of fuel cell, reduces the use of precious metal Pt, enhances the tolerance to high concentration CO, improves the performance stability in strong acids and high temperature environments, and promotes the commercialization of HT-PEMFCs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833648A_ABST
    Figure CN119833648A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an anode catalyst of a low-Pt-loading high-temperature proton exchange membrane fuel cell, an anode diffusion layer and a membrane electrode, and relates to the technical field of fuel cells. Alloy oxide clusters formed in the process do not influence the size of Pt nano-particles, and the binding energy with pt nano-particles can be increased, so that the activity of the catalyst is favorably improved, and the hydroxide reaction is accelerated; based on the anode catalyst for the low-Pt-loading high-temperature proton exchange membrane fuel cell, the microstructure of an electrode is regulated and controlled by designing catalyst slurry, catalyst layer spraying parameters and the like, and the transmission loss between membrane electrodes is reduced by optimally designing a three-phase interface of the membrane electrodes, the loading of noble metal Pt is also effectively reduced, and the phenomena of CO poisoning and phosphoric acid flooding are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a method for preparing an anode catalyst of a low Pt loading high temperature proton exchange membrane fuel cell, an anode diffusion layer and a membrane electrode. Background Art

[0002] A fuel cell is an energy conversion device that can directly convert chemical energy into electrical energy. Its energy conversion is not limited by the Carnot cycle, and the theoretical energy conversion efficiency can reach 90%. Compared with low-temperature proton exchange membrane fuel cells (LT-PEMFCs), high-temperature proton exchange membrane fuel cells (HT-PEMFCs) have an operating temperature of 120-180°C, simple water and heat system management, and higher tolerance to CO poisoning. HT-PEMFCs are highly adaptable to multi-source fuel hydrogen production systems such as methanol, ethanol, and ammonia, and there is no need to cool or purify the crude hydrogen from the reaction, thus avoiding energy waste. The application and promotion of HT-PEMFCs is of great significance to the development of hydrogen energy and carbon conservation and emission reduction.

[0003] The water content in the current commercial HT-PEMFCs system is low, so phosphoric acid-doped polybenzimidazole (PA-PBIs) proton exchange membranes are often used. However, the binding force between phosphoric acid and polybenzimidazole is poor. During long-term operation, phosphoric acid will overflow from the proton exchange membrane to the catalyst layer, causing "acid flooding", occupying the active sites of Pt and reducing the activity of the catalyst. In order to ensure satisfactory performance of the battery, a large amount of precious metal Pt / C catalysts must be used, and its high cost limits the development of HT-PEMFCs.

[0004] On the other hand, if one wants to directly utilize industrial by-product hydrogen containing high concentrations of CO or hydrogen produced by in-situ reforming, there is still the problem of significant performance degradation of HT-PEMFCs.

[0005] Therefore, it is urgent to develop anodes with high catalytic activity, low cost, strong resistance to CO poisoning, low pt loading, tolerance to phosphoric acid deactivation and high concentration CO poisoning in strong acid and high temperature environments, and membrane electrodes that are adaptable to the sealing and performance of the stack under multi-physical fields, so as to achieve stable operation of the stack under complex and changeable working conditions under multi-source (containing impurities) fuel conditions, and accelerate the commercial application and promotion of HT-PEMFCs. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a low Pt loading high temperature proton exchange membrane fuel cell anode catalyst, an anode diffusion layer and a membrane electrode, to solve the following technical problems:

[0007] How to improve the activity of fuel cell anode catalysts and reduce costs.

[0008] The purpose of the present invention can be achieved through the following technical solutions:

[0009] In a first aspect, the present invention discloses a method for preparing a low Pt loading high temperature proton exchange membrane fuel cell anode catalyst, comprising the following steps:

[0010] S1, preparing a mixed aqueous solution of an alloy salt precursor and a carbon carrier, preparing an aqueous solution of chloroplatinic acid, and preparing an aqueous solution of a reducing agent;

[0011] S2, adding 1 / 2 volume of the reducing agent aqueous solution to the mixed aqueous solution of the alloy salt precursor and the carbon support by titration, and mixing evenly to obtain a mixed solution A;

[0012] S3, adding chloroplatinic acid aqueous solution to mixed solution A and mixing evenly to obtain mixed solution B;

[0013] S4. Add the remaining 1 / 2 volume of the reducing agent aqueous solution dropwise into the mixed solution B to react and form a precipitate. Wash the precipitate with water and then perform high-temperature reduction calcination to obtain an anode catalyst.

[0014] Preferably, in step S1, the usage ratio of the alloy salt precursor and the carbon carrier is (35-82):50.

[0015] Preferably, in step S1, the alloy salt precursor is Mo salt, Co salt, Ni salt, Fe salt, and / or.

[0016] Preferably, in step S1, the carbon carrier is carbon black, graphene, Ketjen black, carbon nanotubes, and / or.

[0017] Preferably, in step S1, the total content of the alloy salt precursor and the carbon carrier in the mixed aqueous solution of the alloy salt precursor and the carbon carrier is (0.425-0.66): 100 mL; the content of chloroplatinic acid in the chloroplatinic acid aqueous solution is 0.8 g / 100 mL;

[0018] Preferably, the content of the reducing agent in the reducing agent aqueous solution is 10 g / 100 mL.

[0019] Preferably, in step S4, the temperature of the high-temperature reduction calcination is 400-900° C., and the sintering atmosphere is high-purity nitrogen or a hydrogen-nitrogen mixed gas.

[0020] In the second aspect, the present invention discloses a low Pt loading high temperature proton exchange membrane fuel cell anode diffusion layer, comprising a diffusion layer and a layer of anode catalyst coated on the surface of the diffusion layer, wherein the anode catalyst is prepared by the preparation method of the Pt loading high temperature proton exchange membrane fuel cell anode as described above.

[0021] Preferably, the method for preparing the anode diffusion layer comprises the following steps:

[0022] a. Evenly mixing an anode catalyst, a binder, a dispersing solvent and deionized water to obtain an anode catalyst slurry, wherein the solid content of the anode catalyst slurry is 0.5%-5%, wherein the amount of the binder is 2%-15% of the amount of the anode catalyst;

[0023] b. The catalyst slurry is ultrasonically sprayed on the clean diffusion layer surface to obtain an anode diffusion layer; the Pt loading on the anode diffusion layer is 0.05-0.5 mg / cm 2 .

[0024] Further, in step a, the binder is PTFE, PVDF, FEP, ECTE, ETFE, PFA, and / or;

[0025] Furthermore, the dispersing solvent is anhydrous ethanol, propanol, isopropanol, and / or.

[0026] In a third aspect, the present invention further discloses a membrane electrode for a low Pt loading high temperature proton exchange membrane fuel cell, comprising an anode frame, an anode diffusion layer, a high temperature proton membrane, a cathode diffusion layer, and a cathode frame which are sequentially bonded, wherein the anode diffusion layer is the anode diffusion layer of the low Pt loading high temperature proton exchange membrane fuel cell as described above;

[0027] Preferably, the cathode diffusion layer is prepared by:

[0028] a. Evenly mix the Pt / C catalyst, the binder, the dispersing solvent and the deionized water to obtain a cathode catalyst slurry, wherein the solid content of the cathode catalyst slurry is 0.5%-5%, wherein the amount of the binder is 0.5%-5% of the amount of the anode catalyst;

[0029] b. Ultrasonic spraying of the catalyst slurry on the clean diffusion layer surface to obtain a cathode diffusion layer; the Pt loading on the cathode diffusion layer is 0.5-1.5 mg / cm 2 .

[0030] Further, in step a, the binder is PTFE, PVDF, FEP, ECTE, ETFE, PFA, and / or;

[0031] Furthermore, the dispersing solvent is anhydrous ethanol, propanol, isopropanol, and / or.

[0032] Preferably, the preparation method of the high-temperature proton membrane is: dissolving PBI (polybenzimidazole) powder in DMAC solution, heating and stirring at 160°C for 16 hours until the PBI powder is completely dissolved to obtain a PBI membrane solution, laying the membrane solution by a casting method, and drying it with hot air at 140°C to form a film, cutting the dried dry film into a certain size, soaking it in 85wt% phosphoric acid at 120°C for 2 hours, and wiping off the floating acid on the surface with dust-free paper to obtain a high-temperature proton membrane.

[0033] Furthermore, the thickness of the high temperature proton membrane is 15-55um;

[0034] Preferably, the anode frame is the same as the cathode frame, and the preparation method thereof is: selecting a frame material of suitable thickness, and adopting a hot cutting or knife cutting process to punch and shape it.

[0035] Furthermore, the frame material is PPS, PI, PTFE, and / or.

[0036] Furthermore, the punching and forming is performed by using a heat cutting or knife cutting process, designing a special knife die tool as a tool for punching and forming the membrane electrode, or using ultrasonic cutting, laser cutting, infrared cutting and other processes for punching and forming.

[0037] Preferably, the membrane electrode is prepared by laminating an anode frame, an anode diffusion layer, a high-temperature proton membrane, a cathode diffusion layer, and a cathode frame in sequence to obtain a "five-in-one" membrane electrode.

[0038] Beneficial effects of the present invention:

[0039] 1. In the method for preparing anode catalyst of high-temperature proton exchange membrane fuel cell with low Pt loading according to the present invention, alloy and precious metal platinum are deposited successively by "distributed titration + high-temperature calcination". The alloy oxide clusters formed in the process will not affect the size of Pt nanoparticles, but can also increase the binding ability with Pt nanoparticles, which is helpful to improve the activity of the catalyst and accelerate the hydrogen oxidation reaction.

[0040] 2. Based on the low Pt loading high temperature proton exchange membrane fuel cell anode catalyst prepared by the present invention, the microscopic morphology of the anode diffusion layer is regulated by designing catalyst slurry, catalyst layer spraying parameters, etc., and the transmission loss between the membrane electrode is reduced by optimizing the design of the membrane electrode three-phase interface. It also effectively reduces the loading of the precious metal Pt, improves CO poisoning and phosphoric acid "acid flooding", and provides a way of thinking for the development of low-cost, high-performance, high-temperature proton exchange membrane fuel cells, which is conducive to promoting the commercialization process of HT-PEMFCs. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The present invention will be further described below in conjunction with the accompanying drawings.

[0042] Figure 1 is a SEM image of the microscopic morphology of the PtMo / CNT anode catalyst prepared in Example 1;

[0043] Figure 2 is a TEM image of the microscopic morphology of the PtMo / CNT anode catalyst prepared in Example 1;

[0044] Figure 3 is the energy spectrum of the C element in the PtMo / CNT anode catalyst prepared in Example 1;

[0045] Figure 4 is the energy spectrum of the Pt element in the PtMo / CNT anode catalyst prepared in Example 1;

[0046] Figure 5 is the energy spectrum of the Mo element in the PtMo / CNT anode catalyst prepared in Example 1;

[0047] Figure 6 It is a curve comparison diagram of the polarization performance and power density of the membrane electrodes prepared in Examples 6-8 and Comparative Examples 3-4. DETAILED DESCRIPTION

[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0050] Example 1

[0051] Preparation of low Pt loading high temperature proton exchange membrane fuel cell anode catalyst (PtMo / CNT):

[0052] Step 1: Dissolve 350 mg of ammonium molybdate [(NH4)2MoO4] and 520 mg of carbon nanotubes in 200 ml of deionized water, and disperse them by ultrasonic method for 1 hour to obtain a mixed aqueous solution of ammonium molybdate and carbon nanotubes; Dissolve 800 mg of chloroplatinic acid (H2PtCl6) in 100 ml of deionized water, and disperse them by ultrasonic method for 1 hour to obtain a chloroplatinic acid aqueous solution; Dissolve 10 g of sodium borohydride (NaBH4) in 100 ml of deionized water, and stir well to obtain a sodium borohydride (reducing agent) aqueous solution;

[0053] Step 2: slowly drop 50 ml of sodium borohydride aqueous solution into the mixed aqueous solution of ammonium molybdate and carbon nanotubes and mix until the solution becomes clear to obtain a mixed solution A;

[0054] Step 3, slowly dropwise adding the chloroplatinic acid aqueous solution into the mixed solution A and stirring evenly to obtain a mixed solution B;

[0055] Step 4: Add the remaining 50 ml of sodium borohydride aqueous solution to mixed solution B and stir for 1 hour to form a precipitate. Wash the precipitate with deionized water 5 times and dry it. Then, calcine it at 850°C in a pure nitrogen atmosphere for 2 hours to obtain a PtMo / CNT anode catalyst (based on the total amount of catalyst, the Pt mass fraction is 34%, and the Mo mass fraction is 16%).

[0056] The surface morphology of the obtained PtMo / CNT anode catalyst was observed, and the following results were obtained: Figure 1 The SEM images shown in Figure 2 The TEM image shown above detects the element distribution and obtains Figure 3-5 Energy spectra of C, Pt, and Mo elements are shown.

[0057] Example 2

[0058] Preparation of low Pt loading high temperature proton exchange membrane fuel cell anode catalyst (PtNi / C):

[0059] Step 1: Dissolve 820 mg of nickel nitrate [Ni(NO3)2·6H2O] and 500 mg of carbon black in 200 ml of deionized water, and disperse them ultrasonically for 1 hour to obtain a mixed aqueous solution of nickel nitrate and carbon black; dissolve 800 mg of chloroplatinic acid (H2PtCl6) in 100 ml of deionized water, and disperse them ultrasonically for 1 hour to obtain a chloroplatinic acid aqueous solution; dissolve 10 g of sodium borohydride (NaBH4) in 100 ml of deionized water, and stir evenly to obtain a sodium borohydride (reducing agent) aqueous solution;

[0060] Step 2, slowly drop 50 ml of sodium borohydride aqueous solution into the mixed aqueous solution of nickel nitrate and carbon black and mix until the solution becomes clear to obtain a mixed solution A;

[0061] Step 3, slowly dropwise adding the chloroplatinic acid aqueous solution into the mixed solution A and stirring evenly to obtain a mixed solution B;

[0062] Step 4: Add the remaining 50 ml of sodium borohydride aqueous solution to mixed solution B and stir for 1 hour to form a precipitate. Wash the precipitate with deionized water 5 times and dry it. Then, calcine it at 850°C in a pure nitrogen atmosphere for 2 hours to obtain a PtNi / C anode catalyst (based on the total amount of catalyst, the Pt mass fraction is 34%, and the Ni mass fraction is 16%).

[0063] Comparative Example 1

[0064] Preparation of high temperature proton exchange membrane fuel cell anode catalyst (Pt / CNT):

[0065] Step 1: Dissolve 520 mg of carbon nanotubes in 200 ml of deionized water, and disperse by ultrasonic for 1 hour to obtain a carbon nanotube aqueous solution; dissolve 800 mg of chloroplatinic acid (H2PtCl6) in 100 ml of deionized water, and disperse by ultrasonic for 1 hour to obtain a chloroplatinic acid aqueous solution; dissolve 10 g of sodium borohydride (NaBH4) in 100 ml of deionized water, and stir evenly to obtain a sodium borohydride (reducing agent) aqueous solution;

[0066] Step 2, slowly drop 50 ml of sodium borohydride aqueous solution into the carbon nanotube aqueous solution and mix until the solution becomes clear to obtain a mixed solution A;

[0067] Step 3, slowly dropwise adding the chloroplatinic acid aqueous solution into the mixed solution A and stirring evenly to obtain a mixed solution B;

[0068] Step 4: Add the remaining 50 ml of sodium borohydride aqueous solution to mixed solution B and stir for 1 hour to form a precipitate. Wash the precipitate with deionized water 5 times and dry it. Then, calcine it at 850°C in a pure nitrogen atmosphere for 2 hours to obtain a Pt / CNT anode catalyst (based on the total amount of catalyst, the Pt mass fraction is 50%).

[0069] Example 3

[0070] Preparation of low Pt loading high temperature proton exchange membrane fuel cell anode diffusion layer:

[0071] Step 1, weigh 1g of the PtMo / CNT anode catalyst prepared in Example 1, add 10.46g of deionized water and stir evenly, then add 0.05g of a 60% PTFE aqueous solution, add 94.5g of isopropanol after ultrasonication for 10min, ultrasonicate again for 10min to obtain a mixed slurry, high-speed shear disperse the mixed slurry for 40min, and then disperse it with a high-pressure homogenizer for 10min to obtain an anode catalyst slurry (solid content is 1%);

[0072] Step 2: Cut 50cm 2 Carbon paper, the catalyst slurry was sprayed onto the carbon paper (diffusion layer) by an ultrasonic sprayer, and the pt loading was 0.4 mg / cm by weighing method. 2 .

[0073] Example 4

[0074] Preparation of low Pt loading high temperature proton exchange membrane fuel cell anode diffusion layer:

[0075] Step 1, weigh 1g of the PtNi / C anode catalyst prepared in Example 2, add 5.65g of deionized water and stir evenly, then add 0.25g of a 60% PTFE aqueous solution, add 51.75g ​​of isopropanol after ultrasonic treatment for 10min, ultrasonicate again for 10min to obtain a mixed slurry, high-speed shear disperse the mixed slurry for 40min, and then disperse it with a high-pressure homogenizer for 10min to obtain an anode catalyst slurry (solid content is 2%);

[0076] Step 2: Cut 50cm 2 Carbon paper, the catalyst slurry was sprayed onto the carbon paper (diffusion layer) by an ultrasonic sprayer, and the pt loading was 0.5 mg / cm by weighing method. 2 .

[0077] Example 5

[0078] Preparation of low Pt loading high temperature proton exchange membrane fuel cell anode diffusion layer:

[0079] Step 1, weigh 1g of the PtMo / CNT anode catalyst prepared in Example 1, add 20.967g of deionized water and stir evenly, then add 0.083g of a 60% PTFE aqueous solution by mass, add 189g of isopropanol after ultrasonication for 10min, ultrasonicate again for 10min to obtain a mixed slurry, high-speed shear disperse the mixed slurry for 40min, and then disperse it with a high-pressure homogenizer for 15min to obtain an anode catalyst slurry (solid content of 5%);

[0080] Step 2: Cut 50cm 2 Carbon paper, the catalyst slurry was sprayed onto the carbon paper (diffusion layer) by an ultrasonic sprayer, and the pt loading was 0.05 mg / cm by weighing method. 2 .

[0081] Comparative Example 2

[0082] Preparation of anode diffusion layer:

[0083] Step 1, weigh 1g of the Pt / CNT anode catalyst prepared in Comparative Example 1, add 11.4g of deionized water and stir evenly, then add 0.25g of a 60% PTFE aqueous solution, add 103.5g of isopropanol after ultrasonic treatment for 10min, and then ultrasonic treatment for 10min to obtain a mixed slurry, high-speed shear dispersion of the mixed slurry for 40min, and then disperse it with a high-pressure homogenizer for 15min to obtain an anode catalyst slurry;

[0084] Step 2: Cut 50cm 2 Carbon paper, the catalyst slurry was sprayed onto the carbon paper (diffusion layer) by an ultrasonic sprayer, and the pt loading was 0.7 mg / cm by weighing method. 2 .

[0085] Example 6

[0086] Preparation of low Pt loading high temperature proton exchange membrane fuel cell membrane electrode:

[0087] Step 1: Preparation of cathode diffusion layer

[0088] (1) Preparation of cathode diffusion layer slurry: Pt / C catalyst powder with a Pt mass fraction of 50% was purchased from Jiping New Energy; 1 g of the Pt / C catalyst powder was weighed, 11.4 g of deionized water was added, and the mixture was stirred evenly. Then, 0.25 g of a 60% wt PTFE aqueous solution was added, and 103.5 g of isopropanol was added after ultrasonic treatment for 10 min. After ultrasonic treatment for another 10 min, the mixed slurry was dispersed by high-speed shearing for 40 min and then dispersed by a high-pressure homogenizer for 10 min to prepare a cathode catalyst slurry (solid content of 1%);

[0089] (2) Preparation of cathode diffusion layer: Cut 50 cm 2 Carbon paper, the catalyst slurry was sprayed onto the carbon paper (diffusion layer) by ultrasonic spraying machine, and the pt loading was 0.8 mg / cm by weighing method. 2 .

[0090] Step 2: Preparation of high-temperature proton exchange membrane: 3 g PBI powder was dissolved in 27 g DMAC solution, heated and stirred at 160 ° C for 16 h until the PBI powder was completely dissolved, and a PBI membrane solution with a mass fraction of 10% was obtained. The PBI membrane solution was spread on a clean glass by a casting method, and dried in hot air at 140 ° C to form a dry film with a thickness of 40 μm; the dry film was cut into 50 cm 2 , immersed in 85% phosphoric acid solution at 120°C for 2h, and wiped off the floating acid on the surface of the proton membrane with dust-free paper to obtain a high-temperature proton exchange membrane.

[0091] Step 3: Prepare the anode frame and cathode frame: punch out the frames of PI material with a thickness of 0.1 mm into the required sizes respectively.

[0092] Step 4: Prepare membrane electrode: sequentially bond the anode frame, the anode diffusion layer prepared in Example 3, the high-temperature proton exchange membrane, the cathode diffusion layer, and the cathode frame to obtain a "five-in-one" low Pt loading high-temperature proton exchange membrane fuel cell membrane electrode.

[0093] Example 7

[0094] Preparation of low Pt loading high temperature proton exchange membrane fuel cell membrane electrode:

[0095] Compared with Example 6, the only difference is that the anode diffusion layer prepared in Example 3 in step 4 is replaced by the anode diffusion layer prepared in Example 4, and finally a low Pt loading high temperature proton exchange membrane fuel cell membrane electrode is prepared.

[0096] Example 8

[0097] Preparation of low Pt loading high temperature proton exchange membrane fuel cell membrane electrode:

[0098] Compared with Example 6, the only difference is that the anode diffusion layer prepared in Example 3 in step 4 is replaced by the anode diffusion layer prepared in Example 5, and finally a low Pt loading high temperature proton exchange membrane fuel cell membrane electrode is prepared.

[0099] Comparative Example 3

[0100] Preparation of high temperature proton exchange membrane fuel cell membrane electrode:

[0101] Compared with Example 6, the only difference is that the anode diffusion layer prepared in Example 3 in step 4 is replaced by the cathode diffusion layer prepared in step 1 of Example 6, and finally a high-temperature proton exchange membrane fuel cell membrane electrode is prepared.

[0102] Comparative Example 4

[0103] Preparation of high temperature proton exchange membrane fuel cell membrane electrode:

[0104] Compared with Example 6, the only difference is that the anode diffusion layer prepared in Example 3 in step 4 is replaced by the anode diffusion layer prepared in Comparative Example 2, and finally a high-temperature proton exchange membrane fuel cell membrane electrode is prepared.

[0105] The polarization performance of the high-temperature proton exchange membrane fuel cell membrane electrode prepared in Examples 6-8 and Comparative Examples 3-4 was tested. The test conditions were: the single cell operating temperature was 160°C, the anode air intake was 1% CO + 24% CO2 + 75% H2, the cathode air intake was air feed, and the cathode / anode feeds were 3 / 4 times the stoichiometric ratio, and finally the following was obtained: Figure 6 The polarization performance and power density curve comparison is shown.

[0106] from Figure 6 It can be seen that compared with the high Pt loading membrane electrode of the anode of Comparative Examples 3 and 4 (the anode Pt loading is 0.7-0.8 mg / cm 2 ), Examples 6-8 were performed at low Pt loading (anode Pt loading was 0.05-0.5 mg / cm 2 ), it can still achieve performance effects similar to or even better than those of Comparative Examples 3 and 4, which shows that the low Pt loading high temperature proton exchange membrane fuel cell membrane electrode of the present invention has excellent polarization performance.

[0107] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a low Pt loading high temperature proton exchange membrane fuel cell anode catalyst, characterized in that: The steps include: S1, preparing a mixed aqueous solution of an alloy salt precursor and a carbon carrier, preparing an aqueous solution of chloroplatinic acid, and preparing an aqueous solution of a reducing agent; S2, adding 1 / 2 volume of the reducing agent aqueous solution to the mixed aqueous solution of the alloy salt precursor and the carbon support by titration, and mixing evenly to obtain a mixed solution A; S3, adding chloroplatinic acid aqueous solution to mixed solution A and mixing evenly to obtain mixed solution B; S4. Add the remaining 1 / 2 volume of the reducing agent aqueous solution dropwise into the mixed solution B to react and form a precipitate. Wash the precipitate with water and then perform high-temperature reduction calcination to obtain an anode catalyst.

2. The method for preparing a low Pt loading high temperature proton exchange membrane fuel cell anode catalyst according to claim 1, characterized in that: In step S1, the usage ratio of the alloy salt precursor and the carbon carrier is (35-82):

50.

3. The method for preparing a low Pt loading high temperature proton exchange membrane fuel cell anode catalyst according to claim 2, characterized in that: In step S1, the alloy salt precursor is Mo salt, Co salt, Ni salt, Fe salt, and / or.

4. The method for preparing a low Pt loading high temperature proton exchange membrane fuel cell anode catalyst according to claim 2, characterized in that: In step S1, the carbon carrier is carbon black, graphene, Ketjen black, carbon nanotubes, and / or.

5. The method for preparing a low Pt loading high temperature proton exchange membrane fuel cell anode catalyst according to claim 1, characterized in that: In step S1, the total content of the alloy salt precursor and the carbon carrier in the mixed aqueous solution of the alloy salt precursor and the carbon carrier is (0.425-0.66): 100 mL; the content of chloroplatinic acid in the chloroplatinic acid aqueous solution is 0.8 g / 100 mL; and the content of the reducing agent in the reducing agent aqueous solution is 10 g / 100 mL.

6. The method for preparing a low Pt loading high temperature proton exchange membrane fuel cell anode catalyst according to claim 1, characterized in that: In step S4, the temperature of the high-temperature reduction calcination is 400-900° C., and the sintering atmosphere is high-purity nitrogen or a hydrogen-nitrogen mixed gas.

7. A low Pt loading high temperature proton exchange membrane fuel cell anode diffusion layer, comprising a diffusion layer and a layer of anode catalyst coated on the surface of the diffusion layer, characterized in that: The anode catalyst is prepared by the method for preparing a Pt-loaded high-temperature proton exchange membrane fuel cell anode according to any one of claims 1-6.

8. The low Pt loading high temperature proton exchange membrane fuel cell anode diffusion layer according to claim 7, characterized in that: The method for preparing the anode diffusion layer comprises the following steps: a. Evenly mixing an anode catalyst, a binder, a dispersing solvent and deionized water to obtain an anode catalyst slurry, wherein the solid content of the catalyst slurry is 0.5%-5%, wherein the amount of the binder is 2%-15% of the amount of the anode catalyst; b. The catalyst slurry is ultrasonically sprayed on the clean diffusion layer surface to obtain an anode diffusion layer; the Pt loading on the anode diffusion layer is 0.05-0.5 mg / cm 2 .

9. The low Pt loading high temperature proton exchange membrane fuel cell anode diffusion layer according to claim 8, characterized in that: In step a, the binder is PTFE, PVDF, FEP, ECTE, ETFE, PFA, and / or; the dispersing solvent is anhydrous ethanol, propanol, isopropanol, and / or.

10. A low Pt loading high temperature proton exchange membrane fuel cell membrane electrode, comprising an anode frame, an anode diffusion layer, a high temperature proton membrane, a cathode diffusion layer, and a cathode frame which are bonded in sequence, characterized in that: The anode diffusion layer is the anode diffusion layer of a proton exchange membrane fuel cell with a low Pt loading and a high temperature as described in any one of claims 7-9.